Choice of coverage for restoration thermal mono rails mechanization aircraft wing - Краля, В.О.; Моляр, О.Г.; Хімко, А.М.; Пугачевський, Д.О. (Proceedings of National Aviation University (archive), 2006)
The main tribotechnical characteristics of plasm gasthermal retraction – coatings for restoration of monorail of alloy BT-22 for extension of flaps and slats of modern aircraft are analysed. The parameters of fretting-resistance and adheasive strength of coatings are determined. It is estaflished that the optimal coating is a coating of molibdenum. The results are especially actual for modern aviation industry, as for nowadays there is no common opinion about the given assembly restoration. The monorail recovery of high lift devices by means of plasm covering gives signiticant economic effect and economy of material.